From online to offline education in the post-pandemic era: Challenges encountered by international students at British universities - Zhao, Xin; Xue, Wenchao (Frontiers in Psychology, 2023)
Background After 2 years of anti-pandemic struggles, universities in the United Kingdom have started to witness a reverse transition, a shift from online to offline education. This includes encouraging students to begin face-to-face programmes and allowing flexibility for remote learners, but later requiring all students to return to campus by a certain date. Objectives This paper aims to explore the challenges and impacts brought about by this new transition and provide recommendations for universities to enhance student experience for future adversity. Method This qualitative study conducted semi-structured interviews with 24 international students from a British university to explore their experiences during the transition. The results were analysed using thematic analysis. Results Our data revealed both internal and external challenges to students during the online-to-offline shift, which lead to a general resistance to said shift. Specifically, policy challenges (e.g., policy conflicts) imposed the most significant impacts on international students, resulting in psychological anxiety, financial losses, and negative learning experiences. The reduction of digital tools and learning materials during the shift also presented challenges to students who developed a reliance on digital resources while learning remotely. Other challenges have also been identified, including academic barriers and social engagement issues. Conclusion By highlighting these challenges, this paper has practical implications for university policy decisions and provides recommendations for supporting students’ transition back to traditional offline learning.